2003
DOI: 10.1093/brain/awg267
|View full text |Cite
|
Sign up to set email alerts
|

Patterning of globus pallidus local field potentials differs between Parkinson's disease and dystonia

Abstract: Here we test the hypothesis that there are distinct temporal patterns of synchronized neuronal activity in the pallidum that characterize untreated and treated parkinsonism and dystonia. To this end we recorded local field potentials (LFPs) from the caudal and rostral contact pairs of macroelectrodes implanted into the pallidum of patients for the treatment of Parkinson's disease (12 cases recorded on and off medication, 17 macroelectrodes) and dystonia (10 cases, 19 macroelectrodes). Percentage LFP power in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
259
5
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 396 publications
(291 citation statements)
references
References 54 publications
23
259
5
4
Order By: Relevance
“…The presence of lowfrequency discharge in the GPi in patients with dystonia is similar to that in other hyperkinetic disorders, including chorea/ ballismus and motor tics [197,203,204]. Other studies have shown the emergence of low-frequency oscillations in single-cell and LFP activities in the basal ganglia or thalamus [200,201,[205][206][207], comparable with those found in PD. Electrocorticographic recordings over the MC in patients with isolated dystonia showed less coupling between the phase of beta-band oscillations and the amplitude of gamma-band oscillations than found in patients with PD [208].…”
Section: Dystoniasupporting
confidence: 71%
“…The presence of lowfrequency discharge in the GPi in patients with dystonia is similar to that in other hyperkinetic disorders, including chorea/ ballismus and motor tics [197,203,204]. Other studies have shown the emergence of low-frequency oscillations in single-cell and LFP activities in the basal ganglia or thalamus [200,201,[205][206][207], comparable with those found in PD. Electrocorticographic recordings over the MC in patients with isolated dystonia showed less coupling between the phase of beta-band oscillations and the amplitude of gamma-band oscillations than found in patients with PD [208].…”
Section: Dystoniasupporting
confidence: 71%
“…In addition, the thalamus [39] and the globus pallidus [40] were, according to our first hypothesis, also activated after ACUP on GB 34; however, this was only the case in healthy participants. More specifically, in healthy participants, it was found that almost all brain activation occurred in the basal ganglia.…”
Section: Discussionmentioning
confidence: 60%
“…Based on the literature, we hypothesize that acupuncture stimulation on GB 34 has an effect on brain areas that are known to show dysfunction due to nigral dopamine depletion: the prefrontal cortex [37], precentral gyrus [38], thalamus [39], globus pallidus [40], caudate [41], and putamen [38]. Moreover, our second hypothesis is that a significant difference in brain activity in patients with PD compared with healthy participants will be found.…”
Section: Introductionmentioning
confidence: 96%
“…8,11,14,18,30,32 It is increasingly apparent that the pathophysiology of dystonia extends beyond the basal ganglia. Characteristic findings in the GPi in patients with dystonia, such as irregular discharges 34 and synchronization in low-frequency localfield potentials, 27 represent a snapshot of a wider pattern of dysfunction in functional networks regulating motor control involving the basal ganglia, thalamus, brainstem, cerebellum, and cerebral cortex. 12 The therapeutic mechanism of STN stimulation in dystonia is unknown.…”
Section: Discussionmentioning
confidence: 99%